Treatment with rilpivirine does not alter plasma concentrations of the CYP3A substrates tadalafil and midazolam in humans - Hohmann, Nicolas; Reinhard, Raphael; Schnaidt, Sven; Witt, Lukas; Carls, Alexandra; Burhenne, Jürgen; Mikus, Gerd; Haefeli, Walter E. (The journal of antimicrobial chemotherapy, 2016)
Objectives Antiretroviral combination therapy of patients infected with HIV has greatly increased their life expectancy. Hence, the treatment of HIV-related long-term complications and age-related comorbidities has become more important. Reported incidence rates of erectile dysfunction (ED) and pulmonary arterial hypertension (PAH) are increasing in HIV-positive patients, potentially requiring treatment with phosphodiesterase 5 inhibitors such as sildenafil or tadalafil. In vitro, the NNRTI rilpivirine is both a pregnane X receptor agonist and cytochrome P450 (CYP) 3A inhibitor. Clinical data concerning the potential effects of rilpivirine coadministration on the pharmacokinetics of the CYP3A substrate tadalafil are lacking. Methods We enrolled 20 healthy volunteers in an open-label, two-part, one-arm Phase I clinical trial to investigate acute and chronic effects of multiple doses of 25 mg of oral rilpivirine on single-dose and steady-state pharmacokinetics of multiple oral 20 mg doses of tadalafil. CYP3A activity was measured simultaneously with the oral midazolam microdose test. Results We did not observe a change of tadalafil single-dose and steady-state exposure or of CYP3A activity measured at initiation, during maintenance and upon discontinuation of rilpivirine treatment after single-dose and chronic administration of rilpivirine. Conclusions Tadalafil can be combined with rilpivirine without dose adjustment or drug monitoring in HIV patients with ED or PAH. Rilpivirine at daily therapeutic doses of 25 mg does not induce or inhibit CYP3A-dependent drug metabolism.
Gesehen am 05.01.2017